Watch hollow - Funaro, Gregory (Harper, 2019)
When a mysterious stranger makes their father an offer to fix the clock at Blackford House, Lucy and Oliver Tinker join forces with the magical clock animals to defeat a vicious monster, who wants to take possession of the house.